A STUDY OF JOB SATISFACTION AMONG THE PUBLIC AND PRIVATE UNIVERSITIES: A CASE OF CAPITAL INSTITUTIONS - Misbah Yasmeen; Ansa Nighat Iqbal; Mahek Arshad (International Journal of Contemporary Issues in Social Sciences, 2024)
This relative study investigates the levels of job satisfaction among employees out in the private and public sector universities in Islamabad. Utilizing a quantitative methodology, information was gathered from 447 members through organized polls. Paul E. Spector’s job satisfaction was used to test the variables. The data were analyzed using statistical techniques like t-tests, ANOVA, and regression. Discoveries show that while by and large job satisfaction will in general be respectably higher in private universities, critical varieties exist across unambiguous components of occupation fulfillment. Outstandingly, private sector faculty members announced higher satisfaction levels in regions like advancement, oversight, rewards, collaborator connections, and nature of work. Then again, public area employees revealed higher satisfaction levels in pay and advantages. Additionally, the review recognizes Iqra University as displaying the most noteworthy generally work fulfillment among the overviewed institutions. The exploration highlights the intricacy of variables impacting job satisfaction and gives proposals for encouraging positive workspaces in both public and private sector universities, including the arrangement of motivators, significant work, acknowledgment, and expert improvement professional development opportunities. These discoveries add to the comprehension of job satisfaction elements among university faculty and give experiences to future examination and hierarchical techniques pointed toward improving workforce prosperity and execution.